(untitled) (ENTHYMEMA, 2012)
In this article we present Michail Bakhtin’s ethical and aesthetic philosophy in its original place between phenomenology and hermeneutics. By reflecting on the peculiar “analogic” logic conceived by the Russian thinker, we will show how such a conception manages to put in relationship the subjectivity and the world, the person’s uniqueness and the complex space of culture.